Keterkaitan dan Implikasi Pragmatisme dalam Pendidikan - Nidawati Nidawati (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
The philosophy of Pragmatism states that truth is a theory depending on which is useful or at least the theory is useful for humans in their lives. The birth of the philosophy of Pragmatism was motivated by his criticism of traditional philosophical thoughts. Pragmatism figures such as Charles Sanders Pierce, Willian James and John Dewey, they view human life as a continuous struggle for life and most importantly are practical consequences that are closely related to meaning and truth. In terms of education, pragmatism holds that education is a process of reorganization and reconstruction of individual experiences. The formation of a child's personality is a process of organizing and rebuilding children's experiences, not a process of forming from the outside and not enriching their potential. Education is life itself not preparation for life. Where the goal of education is a good life. The implications of pragmatism education are respecting the principles of education as a basis for experience and subject-centered education